2007
DOI: 10.1109/tuffc.2007.250
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of lamb modes with delaminations in plates coated by highly absorbing materials

Abstract: Abstract-A theoretical study of Lamb mode propagation through an absorptive bilayer consisting of a steel plate coated by highly absorptive rubber with a finite delamination dividing these layers is presented. Essentially, in such a bilayer structure, steel-like A0 and S0 modes still propagate, although with moderate absorption. Two different types of delaminations are taken into consideration: slip delaminations in which noncontact boundary conditions are assumed only for shear displacement and stress, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is obvious that for the numerical evaluation it is necessary to truncate this system to a finite number of local modes. The calculation accuracy could be also quantified by the relative errors of EM energy flow conservation at the interface planes z=(0, L z ) [24]; however, the condition of boundary equations (4a)-(4d) fulfilment is a more general one and this condition leads automatically to EM energy flow conservation fulfilment. It is also important to remark that the EM energy flow is mainly transferred by propagating modes (in the nonabsorptive case even only by propagating modes).…”
Section: Modal Decomposition Methods In a Rectangular Metal Waveguide...mentioning
confidence: 99%
“…It is obvious that for the numerical evaluation it is necessary to truncate this system to a finite number of local modes. The calculation accuracy could be also quantified by the relative errors of EM energy flow conservation at the interface planes z=(0, L z ) [24]; however, the condition of boundary equations (4a)-(4d) fulfilment is a more general one and this condition leads automatically to EM energy flow conservation fulfilment. It is also important to remark that the EM energy flow is mainly transferred by propagating modes (in the nonabsorptive case even only by propagating modes).…”
Section: Modal Decomposition Methods In a Rectangular Metal Waveguide...mentioning
confidence: 99%
“…Koodalil et al 27,28 developed a technique that uses shear horizontal guided waves generated with periodic permanent magnet electromagnetic acoustic transducers (PPM EMATs) to quantify the interfacial adhesion of aluminium-epoxy-aluminium tri-layer in a lap shear joint. Simonetti, 29 Shkerdin and Glorieux 30 and Laperre and Thys 31 presented the theoretical aspects of Lamb wave propagation in bilayer consisting of a metal plate coated by a highly absorptive viscoelastic coating rubber layer. Bostron et al 22 demonstrated the feasibility of guided ultrasonic interface waves (similar to a leaky Rayleigh-like wave on the stiff solid) at a soft–stiff boundary to evaluate the bond between coatings and metal structures using several wave features such as amplitude ratio, pulse width and frequency ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of non-destructive material characterisation, the modal decomposition is often favoured. Shkerdin and Glorieux 1,2 have investigated Lamb mode propagation through a composite plate consisting of two parallel layers of different materials with a finite length delamination. The method to calculate the transmitted and reflected fields was based on a modal expansion of each field in terms of propagating and evanescent modes.…”
Section: Introductionmentioning
confidence: 99%